Preparation method of fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate
By loading sodium percarbonate and ferrous acid sulfate-containing fly ash-Al-MOF materials, the adsorption and oxidation properties of MOF are used to solve the problems of too fast oxidation speed and low oxidation utilization in the prior art, and long-term, stable and effective repair of organic polluted soil is achieved.
Patent Information
- Application Number
- CN202411839574.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
AI Technical Summary
When using sodium percarbonate for soil oxidation repair, the oxidation rate is too fast and the oxidation energy is released in a single way, resulting in low oxidation utilization, inability to effectively repair deep contaminated areas, and may lead to reverse diffusion of pollutants and seizures.
Using fly ash-Al-MOF materials loaded with sodium percarbonate and ferrous acid sulfate, organic pollutants are adsorbed through the high specific surface area and porous properties of MOF, and the oxidative performance is continuously released through the MOF-mounted sodium percarbonate and ferrous acid sulfate.
Long-term, stable, effective and environmentally friendly restoration of organic polluted soil has been achieved, the restoration efficiency has been improved, and the reverse diffusion and trail accumulation of pollutants have been avoided.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of environmental rock and soil technology, and particularly relates to a method for preparing a fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate. Background Art
[0002] Fly ash is a major industrial byproduct produced during the coal-fired power plant combustion process. Its main components are inorganic oxides and a small amount of unburned carbonaceous materials. Due to the huge output of fly ash, its storage and disposal have always been a hot issue in the field of environmental protection and resource utilization. Fly ash can be a potential raw material for the preparation of materials due to its high silicon and aluminum content, especially in the synthesis of porous materials such as metal-organic frameworks (MOFs). Metal-organic frameworks (MOFs) are a new type of materials with high specific surface area, porous properties and adjustable structure. They are widely studied for catalysis, adsorption, separation, storage and as drug carriers. In recent years, researchers have tried to use industrial solid waste such as fly ash as raw materials to synthesize MOF materials, effectively combining the disposal of environmental pollutants with resource recovery to achieve resource utilization of waste.
[0003] In the field of environmental remediation, especially in the treatment of organically contaminated soil, traditional physical, chemical and biological remediation methods have their own limitations. For example, physical methods are costly, chemical methods may produce secondary pollution, and biological remediation is limited by the types of pollutants and environmental conditions. Therefore, the development of an efficient and environmentally friendly remediation agent is of great significance to promote the improvement of soil environmental quality. Sodium percarbonate (SPC), also known as solid hydrogen peroxide, is a white powder or granule that can dissolve rapidly in water and release hydrogen peroxide and carbonate. It is a mild oxidant and is widely used as a bleaching agent and disinfectant in environmental science and industrial applications. In the field of soil remediation, sodium percarbonate is favored for its unique advantages. The hydrogen peroxide and carbonate produced by the decomposition of sodium percarbonate in the environment are harmless to the environment and are a green oxidant. The water and oxygen produced after the decomposition of hydrogen peroxide will not bring secondary pollution to the environment, which is in sharp contrast to the environmental risks that may be caused by traditional chemical oxidants such as chlorine and strong acids. Sodium percarbonate can slowly release hydrogen peroxide at room temperature, which enables it to effectively oxidize organic pollutants without the need for heating or applying high pressure, making the treatment process safer and easier to control. Although sodium percarbonate is a mild oxidant, it still has sufficient oxidizing power to decompose a variety of organic pollutants in soil, including stubborn organic substances such as polycyclic aromatic hydrocarbons and certain stubborn pesticide residues. Sodium percarbonate produces carbonates during the decomposition process, which helps neutralize acidic soils and has a positive effect on improving soil pH balance, which is a feature that many other oxidants do not have. As a solid substance, sodium percarbonate is more stable than liquid hydrogen peroxide and is easy to store and transport. This reduces the danger of handling and use, and also reduces logistics costs. Compared with other oxidants, such as ozone, peracetic acid, chlorine or potassium permanganate, sodium percarbonate has significant advantages such as simple operation, low cost, low impact on the environment and low risk to human health. Other stronger chemical oxidants may require special reaction conditions, such as high temperature or specific pH, and may produce toxic byproducts that require further treatment. In soil remediation, mild oxidants are generally more suitable because they can minimize damage to soil microbial communities and maintain soil biodiversity and ecological balance.
[0004] However, the actual effect of using SPC alone for oxidative remediation is still limited by the characteristics of SPC's fast oxidation speed and single oxidation energy release. The oxidation utilization rate is low and the reaction is quickly consumed. It cannot be added to long-distance and deep contaminated areas through existing in-situ injection equipment. In addition, the instantaneous release characteristics of SPC will cause pollutants in the soil pores to diffuse in reverse, accumulate in tails, and rebound in concentration, reducing the long-term stable effectiveness of using SPC to remove organic pollutants. Summary of the invention
[0005] The object of the present invention is to solve the deficiencies of the above-mentioned prior art and provide a method for preparing a fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate, which realizes the resource utilization of fly ash, and the prepared fly ash-Al-MOF material can achieve long-term, stable, effective and environmentally friendly remediation of organic contaminated soil.
[0006] The present invention combines sodium percarbonate and acid-containing ferrous sulfate with MOF to prepare fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate, which can not only utilize the high specific surface area and porous properties of MOF to adsorb organic pollutants in the soil, but also can use MOF to carry sodium percarbonate and acid-containing ferrous sulfate to achieve continuous release of oxidation performance, thereby achieving effective and environmentally friendly soil remediation. The specific scheme is as follows:
[0007] A method for preparing fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate comprises the following steps:
[0008] (1) heat-treating fly ash, cooling it after completion, and then adding it to a sulfuric acid solution, stirring and mixing it evenly, and then performing solid-liquid separation to obtain a liquid product;
[0009] (2) adding sodium hydroxide to the liquid product obtained in step (1) while stirring to adjust the pH of the system to 4.5-6 to obtain aluminum hydroxide precipitate, washing and calcining the aluminum hydroxide precipitate to obtain aluminum oxide, and stirring and mixing the aluminum oxide with a sulfuric acid solution to obtain an aluminum sulfate solution;
[0010] (3) dissolving phthalic acid in dimethyl sulfoxide to obtain a phthalic acid solution, mixing the phthalic acid solution and the aluminum sulfate solution obtained in step (2) uniformly, and then separating the solid and liquid, washing the obtained solid product, freeze-drying it, and finally grinding and sieving it to obtain fly ash-Al-MOF;
[0011] (4) adding sodium percarbonate to deionized water, mixing uniformly to obtain a sodium percarbonate solution, adding fly ash-Al-MOF, stirring and mixing uniformly, and then separating the solid and liquid, washing the obtained solid product, and freeze-drying it to obtain fly ash-Al-MOF loaded with sodium percarbonate;
[0012] (5) mixing ferrous sulfate, citric acid and deionized water to obtain an acid-containing ferrous sulfate solution, adding fly ash-Al-MOF, stirring and mixing evenly, and then separating the solid and liquid, washing the obtained solid product, and freeze-drying it to obtain fly ash-Al-MOF loaded with acid-containing ferrous sulfate;
[0013] (6) Evenly mixing the fly ash-Al-MOF loaded with sodium percarbonate and the fly ash-Al-MOF loaded with acid-containing ferrous sulfate to obtain;
[0014] In step (3), the mass ratio of phthalic acid to aluminum oxide is 1:(0.5-4).
[0015] Furthermore, in step (1), the heat treatment temperature is 300-400° C. and the time is 20-30 hours.
[0016] Furthermore, in step (1), the concentration of the sulfuric acid solution is 0.4-0.8 mol / L.
[0017] Furthermore, in step (2), the calcination temperature is 1100-1300° C. and the calcination time is 2-4 hours.
[0018] Furthermore, in step (3), the mass ratio of phthalic acid to aluminum oxide is 1:2.
[0019] Furthermore, in steps (3), (4) and (5), the freeze-drying temperature is -50°C.
[0020] Furthermore, in step (4), the mass ratio of sodium percarbonate to fly ash-Al-MOF is 1:1.
[0021] Furthermore, in step (5), the mass ratio of ferrous sulfate to citric acid is 1:2, and the mass ratio of fly ash-Al-MOF to ferrous sulfate is 1:2.
[0022] Furthermore, in step (6), the mass ratio of the fly ash-Al-MOF loaded with sodium percarbonate to the fly ash-Al-MOF loaded with acid-containing ferrous sulfate is 1:(1.5-3).
[0023] Application of fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate prepared by the above method in repairing organic contaminated soil: air-dry the organic contaminated soil and remove large stones, then test the moisture content and organic pollutant concentration of the organic contaminated soil, add the fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate prepared by the above method according to the tested organic pollutant concentration, stir evenly, add deionized water to adjust the moisture content to 24-28%, and maintain for 7 days to obtain the repaired soil;
[0024] The amount of fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate added is determined according to the concentration of organic pollutants, specifically: when the concentration of organic pollutants is ≤5000 mg / kg, the amount of fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate added is 3% of the total mass of the organic polluted soil; when the concentration of organic pollutants is 5000 mg / kg<the concentration of organic pollutants is ≤10000 mg / kg, the amount of fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate added is 5% of the total mass of the organic polluted soil; when the concentration of organic pollutants is 10000 mg / kg<the concentration of organic pollutants is ≤15000 mg / kg, the amount of fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate added is 8% of the total mass of the organic polluted soil; when the concentration of organic pollutants is greater than 15000 mg / kg, the amount of fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate needs to be increased by 3% for every 5000 mg / kg increase in concentration.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1) The present invention uses solid waste fly ash as a raw material to prepare fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate. The method realizes the resource utilization of solid waste, which can not only turn waste into treasure, but also reduce waste treatment costs and alleviate environmental pressure.
[0027] 2) The present invention combines sodium percarbonate and acid-containing ferrous sulfate with MOF, which can not only utilize the high specific surface area and porous properties of MOF to adsorb organic pollutants in the soil, but also use MOF to carry sodium percarbonate and acid-containing ferrous sulfate to achieve continuous release of oxidative properties, thereby achieving effective and environmentally friendly soil remediation.
[0028] 3) The fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate prepared by the present invention can achieve long-term, stable, effective and environmentally friendly remediation of organic contaminated soil with high remediation efficiency. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the embodiments.
[0030] In the following examples, the fly ash used comes from a coal-fired power plant, and its specific composition is shown in Table 1:
[0031] Table 1
[0032]
[0033] Example 1
[0034] A method for preparing fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate comprises the following steps:
[0035] (1) 50 g of fly ash was placed in a muffle furnace and heat treated at 300° C. for 24 h. After the treatment, it was cooled and then added to a 0.6 mol / L sulfuric acid solution. The mixture was stirred at 70 r / min for 40 min and then solid-liquid separation was performed to obtain a liquid product.
[0036] (2) adding sodium hydroxide to the liquid product obtained in step (1) while stirring to adjust the pH of the system to 4.7 to obtain aluminum hydroxide precipitate, washing the aluminum hydroxide precipitate five times, and calcining it in a muffle furnace at 1200° C. for 3 h to obtain aluminum oxide, taking 50 g of the aluminum oxide and stirring and mixing it with a 0.4 mol / L sulfuric acid solution to obtain an aluminum sulfate solution;
[0037] (3) dissolving 100 g of phthalic acid in dimethyl sulfoxide to obtain a phthalic acid solution, and mixing the phthalic acid solution and the aluminum sulfate solution obtained in step (2) under ultrasonic shearing conditions, wherein the ultrasonic power is 120 W, the ultrasonic time is 40 min, the shear speed is 80 r / min, and the shear stirring time is 40 min, and then solid-liquid separation is performed, and the obtained solid product is washed 5 times with dimethyl sulfoxide, and then freeze-dried at -50°C, and finally ground and sieved to obtain fly ash-Al-MOF;
[0038] (4) adding 12 g of sodium percarbonate to 100 g of deionized water, mixing well to obtain a sodium percarbonate solution, adding 12 g of fly ash-Al-MOF, stirring and mixing well to separate the solid and liquid, washing the obtained solid product with deionized water for 5 times, and freeze-drying at -50°C to obtain fly ash-Al-MOF loaded with sodium percarbonate;
[0039] (5) 24 g of ferrous sulfate, 48 g of citric acid and 100 g of deionized water were mixed to obtain an acid-containing ferrous sulfate solution, 12 g of fly ash-Al-MOF was added, and the mixture was stirred and mixed to obtain solid-liquid separation. The obtained solid product was washed with deionized water for 5 times, and then freeze-dried at -50°C to obtain fly ash-Al-MOF loaded with acid-containing ferrous sulfate;
[0040] (6) The fly ash-Al-MOF loaded with sodium percarbonate and the fly ash-Al-MOF loaded with acid-containing ferrous sulfate were uniformly mixed in a mass ratio of 1:1.5 to obtain a 3D-PUF.
[0041] Example 2
[0042] A method for preparing fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate comprises the following steps:
[0043] (1) 50 g of fly ash was placed in a muffle furnace and heat treated at 300° C. for 24 h. After the treatment, it was cooled and then added to a 0.6 mol / L sulfuric acid solution. The mixture was stirred at 70 r / min for 40 min and then solid-liquid separation was performed to obtain a liquid product.
[0044] (2) adding sodium hydroxide to the liquid product obtained in step (1) while stirring to adjust the pH of the system to 4.7 to obtain aluminum hydroxide precipitate, washing the aluminum hydroxide precipitate five times, and calcining it in a muffle furnace at 1200° C. for 3 h to obtain aluminum oxide, taking 50 g of the aluminum oxide and stirring and mixing it with a 0.4 mol / L sulfuric acid solution to obtain an aluminum sulfate solution;
[0045] (3) dissolving 50 g of phthalic acid in dimethyl sulfoxide to obtain a phthalic acid solution, and mixing the phthalic acid solution and the aluminum sulfate solution obtained in step (2) under ultrasonic shearing conditions, wherein the ultrasonic power is 120 W, the ultrasonic time is 40 min, the shear speed is 80 r / min, and the shear stirring time is 40 min. Then, solid-liquid separation is performed, and the obtained solid product is washed 5 times with dimethyl sulfoxide, and then freeze-dried at -50°C, and finally ground and sieved to obtain fly ash-Al-MOF;
[0046] (4) adding 12 g of sodium percarbonate to 100 g of deionized water, mixing well to obtain a sodium percarbonate solution, adding 12 g of fly ash-Al-MOF, stirring and mixing well to separate the solid and liquid, washing the obtained solid product with deionized water for 5 times, and freeze-drying at -50°C to obtain fly ash-Al-MOF loaded with sodium percarbonate;
[0047] (5) 24 g of ferrous sulfate, 48 g of citric acid and 100 g of deionized water were mixed to obtain an acid-containing ferrous sulfate solution, 12 g of fly ash-Al-MOF was added, and the mixture was stirred and mixed to obtain solid-liquid separation. The obtained solid product was washed with deionized water for 5 times, and then freeze-dried at -50°C to obtain fly ash-Al-MOF loaded with acid-containing ferrous sulfate;
[0048] (6) The fly ash-Al-MOF loaded with sodium percarbonate and the fly ash-Al-MOF loaded with acid-containing ferrous sulfate were uniformly mixed in a mass ratio of 1:1.5 to obtain a 3D-PUF.
[0049] Example 3
[0050] A method for preparing fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate comprises the following steps:
[0051] (1) 50 g of fly ash was placed in a muffle furnace and heat treated at 300° C. for 24 h. After the treatment, it was cooled and then added to a 0.6 mol / L sulfuric acid solution. The mixture was stirred at 70 r / min for 40 min and then solid-liquid separation was performed to obtain a liquid product.
[0052] (2) adding sodium hydroxide to the liquid product obtained in step (1) while stirring to adjust the pH of the system to 4.7 to obtain aluminum hydroxide precipitate, washing the aluminum hydroxide precipitate five times, and calcining it in a muffle furnace at 1200° C. for 3 h to obtain aluminum oxide, taking 50 g of the aluminum oxide and stirring and mixing it with a 0.4 mol / L sulfuric acid solution to obtain an aluminum sulfate solution;
[0053] (3) dissolving 25 g of phthalic acid in dimethyl sulfoxide to obtain a phthalic acid solution, and mixing the phthalic acid solution and the aluminum sulfate solution obtained in step (2) under ultrasonic shearing conditions, wherein the ultrasonic power is 120 W, the ultrasonic time is 40 min, the shear speed is 80 r / min, and the shear stirring time is 40 min, and then the solid-liquid separation is performed, and the obtained solid product is washed 5 times with dimethyl sulfoxide, and then freeze-dried at -50°C, and finally ground and sieved to obtain fly ash-Al-MOF;
[0054] (4) adding 12 g of sodium percarbonate to 100 g of deionized water, mixing well to obtain a sodium percarbonate solution, adding 12 g of fly ash-Al-MOF, stirring and mixing well to separate the solid and liquid, washing the obtained solid product with deionized water for 5 times, and freeze-drying at -50°C to obtain fly ash-Al-MOF loaded with sodium percarbonate;
[0055] (5) 24 g of ferrous sulfate, 48 g of citric acid and 100 g of deionized water were mixed to obtain an acid-containing ferrous sulfate solution, 12 g of fly ash-Al-MOF was added, and the mixture was stirred and mixed to obtain solid-liquid separation. The obtained solid product was washed with deionized water for 5 times, and then freeze-dried at -50°C to obtain fly ash-Al-MOF loaded with acid-containing ferrous sulfate;
[0056] (6) The fly ash-Al-MOF loaded with sodium percarbonate and the fly ash-Al-MOF loaded with acid-containing ferrous sulfate were uniformly mixed in a mass ratio of 1:1.5 to obtain a 3D-PUF.
[0057] Example 4
[0058] A method for preparing fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate comprises the following steps:
[0059] (1) 50 g of fly ash was placed in a muffle furnace and heat treated at 300° C. for 24 h. After the treatment, it was cooled and then added to a 0.6 mol / L sulfuric acid solution. The mixture was stirred at 70 r / min for 40 min and then solid-liquid separation was performed to obtain a liquid product.
[0060] (2) adding sodium hydroxide to the liquid product obtained in step (1) while stirring to adjust the pH of the system to 4.7 to obtain aluminum hydroxide precipitate, washing the aluminum hydroxide precipitate five times, and calcining it in a muffle furnace at 1200° C. for 3 h to obtain aluminum oxide, taking 50 g of the aluminum oxide and stirring and mixing it with a 0.4 mol / L sulfuric acid solution to obtain an aluminum sulfate solution;
[0061] (3) dissolving 12.5 g of phthalic acid in dimethyl sulfoxide to obtain a phthalic acid solution, and mixing the phthalic acid solution and the aluminum sulfate solution obtained in step (2) under ultrasonic shearing conditions, wherein the ultrasonic power is 120 W, the ultrasonic time is 40 min, the shear speed is 80 r / min, and the shear stirring time is 40 min. Then, solid-liquid separation is performed, and the obtained solid product is washed 5 times with dimethyl sulfoxide, and then freeze-dried at -50°C, and finally ground and sieved to obtain fly ash-Al-MOF;
[0062] (4) adding 12 g of sodium percarbonate to 100 g of deionized water, mixing well to obtain a sodium percarbonate solution, adding 12 g of fly ash-Al-MOF, stirring and mixing well to separate the solid and liquid, washing the obtained solid product with deionized water for 5 times, and freeze-drying at -50°C to obtain fly ash-Al-MOF loaded with sodium percarbonate;
[0063] (5) 24 g of ferrous sulfate, 48 g of citric acid and 100 g of deionized water were mixed to obtain an acid-containing ferrous sulfate solution, 12 g of fly ash-Al-MOF was added, and the mixture was stirred and mixed to obtain solid-liquid separation. The obtained solid product was washed with deionized water for 5 times, and then freeze-dried at -50°C to obtain fly ash-Al-MOF loaded with acid-containing ferrous sulfate;
[0064] (6) The fly ash-Al-MOF loaded with sodium percarbonate and the fly ash-Al-MOF loaded with acid-containing ferrous sulfate were uniformly mixed in a mass ratio of 1:1.5 to obtain a 3D-PUF.
[0065] Example 5
[0066] A method for preparing fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate comprises the following steps:
[0067] (1) 50 g of fly ash was placed in a muffle furnace and heat treated at 300° C. for 24 h. After the treatment, it was cooled and then added to a 0.6 mol / L sulfuric acid solution. The mixture was stirred at 70 r / min for 40 min and then solid-liquid separation was performed to obtain a liquid product.
[0068] (2) adding sodium hydroxide to the liquid product obtained in step (1) while stirring to adjust the pH of the system to 4.7 to obtain aluminum hydroxide precipitate, washing the aluminum hydroxide precipitate five times, and calcining it in a muffle furnace at 1200° C. for 3 h to obtain aluminum oxide, taking 50 g of the aluminum oxide and stirring and mixing it with a 0.4 mol / L sulfuric acid solution to obtain an aluminum sulfate solution;
[0069] (3) dissolving 100 g of phthalic acid in dimethyl sulfoxide to obtain a phthalic acid solution, and mixing the phthalic acid solution and the aluminum sulfate solution obtained in step (2) under ultrasonic shearing conditions, wherein the ultrasonic power is 120 W, the ultrasonic time is 40 min, the shear speed is 80 r / min, and the shear stirring time is 40 min, and then solid-liquid separation is performed, and the obtained solid product is washed 5 times with dimethyl sulfoxide, and then freeze-dried at -50°C, and finally ground and sieved to obtain fly ash-Al-MOF;
[0070] (4) adding 12 g of sodium percarbonate to 100 g of deionized water, mixing well to obtain a sodium percarbonate solution, adding 12 g of fly ash-Al-MOF, stirring and mixing well to separate the solid and liquid, washing the obtained solid product with deionized water for 5 times, and freeze-drying at -50°C to obtain fly ash-Al-MOF loaded with sodium percarbonate;
[0071] (5) 24 g of ferrous sulfate, 48 g of citric acid and 100 g of deionized water were mixed to obtain an acid-containing ferrous sulfate solution, 12 g of fly ash-Al-MOF was added, and the mixture was stirred and mixed to obtain solid-liquid separation. The obtained solid product was washed with deionized water for 5 times, and then freeze-dried at -50°C to obtain fly ash-Al-MOF loaded with acid-containing ferrous sulfate;
[0072] (6) The fly ash-Al-MOF loaded with sodium percarbonate and the fly ash-Al-MOF loaded with acid-containing ferrous sulfate are uniformly mixed in a mass ratio of 1:2 to obtain a 3D-PUF.
[0073] Example 6
[0074] A method for preparing fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate comprises the following steps:
[0075] (1) 50 g of fly ash was placed in a muffle furnace and heat treated at 300° C. for 24 h. After the treatment, it was cooled and then added to a 0.6 mol / L sulfuric acid solution. The mixture was stirred at 70 r / min for 40 min and then solid-liquid separation was performed to obtain a liquid product.
[0076] (2) adding sodium hydroxide to the liquid product obtained in step (1) while stirring to adjust the pH of the system to 4.7 to obtain aluminum hydroxide precipitate, washing the aluminum hydroxide precipitate five times, and calcining it in a muffle furnace at 1200° C. for 3 h to obtain aluminum oxide, taking 50 g of the aluminum oxide and stirring and mixing it with a 0.4 mol / L sulfuric acid solution to obtain an aluminum sulfate solution;
[0077] (3) dissolving 50 g of phthalic acid in dimethyl sulfoxide to obtain a phthalic acid solution, and mixing the phthalic acid solution and the aluminum sulfate solution obtained in step (2) under ultrasonic shearing conditions, wherein the ultrasonic power is 120 W, the ultrasonic time is 40 min, the shear speed is 80 r / min, and the shear stirring time is 40 min. Then, solid-liquid separation is performed, and the obtained solid product is washed 5 times with dimethyl sulfoxide, and then freeze-dried at -50°C, and finally ground and sieved to obtain fly ash-Al-MOF;
[0078] (4) adding 12 g of sodium percarbonate to 100 g of deionized water, mixing well to obtain a sodium percarbonate solution, adding 12 g of fly ash-Al-MOF, stirring and mixing well to separate the solid and liquid, washing the obtained solid product with deionized water for 5 times, and freeze-drying at -50°C to obtain fly ash-Al-MOF loaded with sodium percarbonate;
[0079] (5) 24 g of ferrous sulfate, 48 g of citric acid and 100 g of deionized water were mixed to obtain an acid-containing ferrous sulfate solution, 12 g of fly ash-Al-MOF was added, and the mixture was stirred and mixed to obtain solid-liquid separation. The obtained solid product was washed with deionized water for 5 times, and then freeze-dried at -50°C to obtain fly ash-Al-MOF loaded with acid-containing ferrous sulfate;
[0080] (6) The fly ash-Al-MOF loaded with sodium percarbonate and the fly ash-Al-MOF loaded with acid-containing ferrous sulfate are uniformly mixed in a mass ratio of 1:2 to obtain a 3D-PUF.
[0081] Example 7
[0082] A method for preparing fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate comprises the following steps:
[0083] (1) 50 g of fly ash was placed in a muffle furnace and heat treated at 300° C. for 24 h. After the treatment, it was cooled and then added to a 0.6 mol / L sulfuric acid solution. The mixture was stirred at 70 r / min for 40 min and then solid-liquid separation was performed to obtain a liquid product.
[0084] (2) adding sodium hydroxide to the liquid product obtained in step (1) while stirring to adjust the pH of the system to 4.7 to obtain aluminum hydroxide precipitate, washing the aluminum hydroxide precipitate five times, and calcining it in a muffle furnace at 1200° C. for 3 h to obtain aluminum oxide, taking 50 g of the aluminum oxide and stirring and mixing it with a 0.4 mol / L sulfuric acid solution to obtain an aluminum sulfate solution;
[0085] (3) dissolving 25 g of phthalic acid in dimethyl sulfoxide to obtain a phthalic acid solution, and mixing the phthalic acid solution and the aluminum sulfate solution obtained in step (2) under ultrasonic shearing conditions, wherein the ultrasonic power is 120 W, the ultrasonic time is 40 min, the shear speed is 80 r / min, and the shear stirring time is 40 min, and then the solid-liquid separation is performed, and the obtained solid product is washed 5 times with dimethyl sulfoxide, and then freeze-dried at -50°C, and finally ground and sieved to obtain fly ash-Al-MOF;
[0086] (4) adding 12 g of sodium percarbonate to 100 g of deionized water, mixing well to obtain a sodium percarbonate solution, adding 12 g of fly ash-Al-MOF, stirring and mixing well to separate the solid and liquid, washing the obtained solid product with deionized water for 5 times, and freeze-drying at -50°C to obtain fly ash-Al-MOF loaded with sodium percarbonate;
[0087] (5) 24 g of ferrous sulfate, 48 g of citric acid and 100 g of deionized water were mixed to obtain an acid-containing ferrous sulfate solution, 12 g of fly ash-Al-MOF was added, and the mixture was stirred and mixed to obtain solid-liquid separation. The obtained solid product was washed with deionized water for 5 times, and then freeze-dried at -50°C to obtain fly ash-Al-MOF loaded with acid-containing ferrous sulfate;
[0088] (6) The fly ash-Al-MOF loaded with sodium percarbonate and the fly ash-Al-MOF loaded with acid-containing ferrous sulfate are uniformly mixed in a mass ratio of 1:2 to obtain a 3D-PUF.
[0089] Example 8
[0090] A method for preparing fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate comprises the following steps:
[0091] (1) 50 g of fly ash was placed in a muffle furnace and heat treated at 300° C. for 24 h. After the treatment, it was cooled and then added to a 0.6 mol / L sulfuric acid solution. The mixture was stirred at 70 r / min for 40 min and then solid-liquid separation was performed to obtain a liquid product.
[0092] (2) adding sodium hydroxide to the liquid product obtained in step (1) while stirring to adjust the pH of the system to 4.7 to obtain aluminum hydroxide precipitate, washing the aluminum hydroxide precipitate five times, and calcining it in a muffle furnace at 1200° C. for 3 h to obtain aluminum oxide, taking 50 g of the aluminum oxide and stirring and mixing it with a 0.4 mol / L sulfuric acid solution to obtain an aluminum sulfate solution;
[0093] (3) dissolving 12.5 g of phthalic acid in dimethyl sulfoxide to obtain a phthalic acid solution, and mixing the phthalic acid solution and the aluminum sulfate solution obtained in step (2) under ultrasonic shearing conditions, wherein the ultrasonic power is 120 W, the ultrasonic time is 40 min, the shear speed is 80 r / min, and the shear stirring time is 40 min. Then, solid-liquid separation is performed, and the obtained solid product is washed 5 times with dimethyl sulfoxide, and then freeze-dried at -50°C, and finally ground and sieved to obtain fly ash-Al-MOF;
[0094] (4) adding 12 g of sodium percarbonate to 100 g of deionized water, mixing well to obtain a sodium percarbonate solution, adding 12 g of fly ash-Al-MOF, stirring and mixing well to separate the solid and liquid, washing the obtained solid product with deionized water for 5 times, and freeze-drying at -50°C to obtain fly ash-Al-MOF loaded with sodium percarbonate;
[0095] (5) 24 g of ferrous sulfate, 48 g of citric acid and 100 g of deionized water were mixed to obtain an acid-containing ferrous sulfate solution, 12 g of fly ash-Al-MOF was added, and the mixture was stirred and mixed to obtain solid-liquid separation. The obtained solid product was washed with deionized water for 5 times, and then freeze-dried at -50°C to obtain fly ash-Al-MOF loaded with acid-containing ferrous sulfate;
[0096] (6) The fly ash-Al-MOF loaded with sodium percarbonate and the fly ash-Al-MOF loaded with acid-containing ferrous sulfate are uniformly mixed in a mass ratio of 1:2 to obtain a 3D-PUF.
[0097] Example 9
[0098] A method for preparing fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate comprises the following steps:
[0099] (1) 50 g of fly ash was placed in a muffle furnace and heat treated at 300° C. for 24 h. After the treatment, it was cooled and then added to a 0.6 mol / L sulfuric acid solution. The mixture was stirred at 70 r / min for 40 min and then solid-liquid separation was performed to obtain a liquid product.
[0100] (2) adding sodium hydroxide to the liquid product obtained in step (1) while stirring to adjust the pH of the system to 4.7 to obtain aluminum hydroxide precipitate, washing the aluminum hydroxide precipitate five times, and calcining it in a muffle furnace at 1200° C. for 3 h to obtain aluminum oxide, taking 50 g of the aluminum oxide and stirring and mixing it with a 0.4 mol / L sulfuric acid solution to obtain an aluminum sulfate solution;
[0101] (3) dissolving 100 g of phthalic acid in dimethyl sulfoxide to obtain a phthalic acid solution, and mixing the phthalic acid solution and the aluminum sulfate solution obtained in step (2) under ultrasonic shearing conditions, wherein the ultrasonic power is 120 W, the ultrasonic time is 40 min, the shear speed is 80 r / min, and the shear stirring time is 40 min, and then solid-liquid separation is performed, and the obtained solid product is washed 5 times with dimethyl sulfoxide, and then freeze-dried at -50°C, and finally ground and sieved to obtain fly ash-Al-MOF;
[0102] (4) adding 12 g of sodium percarbonate to 100 g of deionized water, mixing well to obtain a sodium percarbonate solution, adding 12 g of fly ash-Al-MOF, stirring and mixing well to separate the solid and liquid, washing the obtained solid product with deionized water for 5 times, and freeze-drying at -50°C to obtain fly ash-Al-MOF loaded with sodium percarbonate;
[0103] (5) 24 g of ferrous sulfate, 48 g of citric acid and 100 g of deionized water were mixed to obtain an acid-containing ferrous sulfate solution, 12 g of fly ash-Al-MOF was added, and the mixture was stirred and mixed to obtain solid-liquid separation. The obtained solid product was washed with deionized water for 5 times, and then freeze-dried at -50°C to obtain fly ash-Al-MOF loaded with acid-containing ferrous sulfate;
[0104] (6) The fly ash-Al-MOF loaded with sodium percarbonate and the fly ash-Al-MOF loaded with acid-containing ferrous sulfate are uniformly mixed in a mass ratio of 1:3 to obtain a 3D MOF.
[0105] Example 10
[0106] A method for preparing fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate comprises the following steps:
[0107] (1) 50 g of fly ash was placed in a muffle furnace and heat treated at 300° C. for 24 h. After the treatment, it was cooled and then added to a 0.6 mol / L sulfuric acid solution. The mixture was stirred at 70 r / min for 40 min and then solid-liquid separation was performed to obtain a liquid product.
[0108] (2) adding sodium hydroxide to the liquid product obtained in step (1) while stirring to adjust the pH of the system to 4.7 to obtain aluminum hydroxide precipitate, washing the aluminum hydroxide precipitate five times, and calcining it in a muffle furnace at 1200° C. for 3 h to obtain aluminum oxide, taking 50 g of the aluminum oxide and stirring and mixing it with a 0.4 mol / L sulfuric acid solution to obtain an aluminum sulfate solution;
[0109] (3) dissolving 50 g of phthalic acid in dimethyl sulfoxide to obtain a phthalic acid solution, and mixing the phthalic acid solution and the aluminum sulfate solution obtained in step (2) under ultrasonic shearing conditions, wherein the ultrasonic power is 120 W, the ultrasonic time is 40 min, the shear speed is 80 r / min, and the shear stirring time is 40 min. Then, solid-liquid separation is performed, and the obtained solid product is washed 5 times with dimethyl sulfoxide, and then freeze-dried at -50°C, and finally ground and sieved to obtain fly ash-Al-MOF;
[0110] (4) adding 12 g of sodium percarbonate to 100 g of deionized water, mixing well to obtain a sodium percarbonate solution, adding 12 g of fly ash-Al-MOF, stirring and mixing well to separate the solid and liquid, washing the obtained solid product with deionized water for 5 times, and freeze-drying at -50°C to obtain fly ash-Al-MOF loaded with sodium percarbonate;
[0111] (5) 24 g of ferrous sulfate, 48 g of citric acid and 100 g of deionized water were mixed to obtain an acid-containing ferrous sulfate solution, 12 g of fly ash-Al-MOF was added, and the mixture was stirred and mixed to obtain solid-liquid separation. The obtained solid product was washed with deionized water for 5 times, and then freeze-dried at -50°C to obtain fly ash-Al-MOF loaded with acid-containing ferrous sulfate;
[0112] (6) The fly ash-Al-MOF loaded with sodium percarbonate and the fly ash-Al-MOF loaded with acid-containing ferrous sulfate are uniformly mixed in a mass ratio of 1:3 to obtain a 3D MOF.
[0113] Embodiment 11
[0114] A method for preparing fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate comprises the following steps:
[0115] (1) 50 g of fly ash was placed in a muffle furnace and heat treated at 300° C. for 24 h. After the treatment, it was cooled and then added to a 0.6 mol / L sulfuric acid solution. The mixture was stirred at 70 r / min for 40 min and then solid-liquid separation was performed to obtain a liquid product.
[0116] (2) adding sodium hydroxide to the liquid product obtained in step (1) while stirring to adjust the pH of the system to 4.7 to obtain aluminum hydroxide precipitate, washing the aluminum hydroxide precipitate five times, and calcining it in a muffle furnace at 1200° C. for 3 h to obtain aluminum oxide, taking 50 g of the aluminum oxide and stirring and mixing it with a 0.4 mol / L sulfuric acid solution to obtain an aluminum sulfate solution;
[0117] (3) dissolving 25 g of phthalic acid in dimethyl sulfoxide to obtain a phthalic acid solution, and mixing the phthalic acid solution and the aluminum sulfate solution obtained in step (2) under ultrasonic shearing conditions, wherein the ultrasonic power is 120 W, the ultrasonic time is 40 min, the shear speed is 80 r / min, and the shear stirring time is 40 min, and then the solid-liquid separation is performed, and the obtained solid product is washed 5 times with dimethyl sulfoxide, and then freeze-dried at -50°C, and finally ground and sieved to obtain fly ash-Al-MOF;
[0118] (4) adding 12 g of sodium percarbonate to 100 g of deionized water, mixing well to obtain a sodium percarbonate solution, adding 12 g of fly ash-Al-MOF, stirring and mixing well to separate the solid and liquid, washing the obtained solid product with deionized water for 5 times, and freeze-drying at -50°C to obtain fly ash-Al-MOF loaded with sodium percarbonate;
[0119] (5) 24 g of ferrous sulfate, 48 g of citric acid and 100 g of deionized water were mixed to obtain an acid-containing ferrous sulfate solution, 12 g of fly ash-Al-MOF was added, and the mixture was stirred and mixed to obtain solid-liquid separation. The obtained solid product was washed with deionized water for 5 times, and then freeze-dried at -50°C to obtain fly ash-Al-MOF loaded with acid-containing ferrous sulfate;
[0120] (6) The fly ash-Al-MOF loaded with sodium percarbonate and the fly ash-Al-MOF loaded with acid-containing ferrous sulfate are uniformly mixed in a mass ratio of 1:3 to obtain a 3D MOF.
[0121] Example 12
[0122] A method for preparing fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate comprises the following steps:
[0123] (1) 50 g of fly ash was placed in a muffle furnace and heat treated at 300° C. for 24 h. After the treatment, it was cooled and then added to a 0.6 mol / L sulfuric acid solution. The mixture was stirred at 70 r / min for 40 min and then solid-liquid separation was performed to obtain a liquid product.
[0124] (2) adding sodium hydroxide to the liquid product obtained in step (1) while stirring to adjust the pH of the system to 4.7 to obtain aluminum hydroxide precipitate, washing the aluminum hydroxide precipitate five times, and calcining it in a muffle furnace at 1200° C. for 3 h to obtain aluminum oxide, taking 50 g of the aluminum oxide and stirring and mixing it with a 0.4 mol / L sulfuric acid solution to obtain an aluminum sulfate solution;
[0125] (3) dissolving 12.5 g of phthalic acid in dimethyl sulfoxide to obtain a phthalic acid solution, and mixing the phthalic acid solution and the aluminum sulfate solution obtained in step (2) under ultrasonic shearing conditions, wherein the ultrasonic power is 120 W, the ultrasonic time is 40 min, the shear speed is 80 r / min, and the shear stirring time is 40 min. Then, solid-liquid separation is performed, and the obtained solid product is washed 5 times with dimethyl sulfoxide, and then freeze-dried at -50°C, and finally ground and sieved to obtain fly ash-Al-MOF;
[0126] (4) adding 12 g of sodium percarbonate to 100 g of deionized water, mixing well to obtain a sodium percarbonate solution, adding 12 g of fly ash-Al-MOF, stirring and mixing well to separate the solid and liquid, washing the obtained solid product with deionized water for 5 times, and freeze-drying at -50°C to obtain fly ash-Al-MOF loaded with sodium percarbonate;
[0127] (5) 24 g of ferrous sulfate, 48 g of citric acid and 100 g of deionized water were mixed to obtain an acid-containing ferrous sulfate solution, 12 g of fly ash-Al-MOF was added, and the mixture was stirred and mixed to obtain solid-liquid separation. The obtained solid product was washed with deionized water for 5 times, and then freeze-dried at -50°C to obtain fly ash-Al-MOF loaded with acid-containing ferrous sulfate;
[0128] (6) The fly ash-Al-MOF loaded with sodium percarbonate and the fly ash-Al-MOF loaded with acid-containing ferrous sulfate are uniformly mixed in a mass ratio of 1:3 to obtain a 3D MOF.
[0129] Comparative Example 1
[0130] Sodium percarbonate was used as Comparative Example 1.
[0131] Comparative Example 2
[0132] A method for preparing fly ash-Al-MOF material loaded with sodium percarbonate comprises the following steps:
[0133] (1) 50 g of fly ash was placed in a muffle furnace and heat treated at 300° C. for 24 h. After the treatment, it was cooled and then added to a 0.6 mol / L sulfuric acid solution. The mixture was stirred at 70 r / min for 40 min and then solid-liquid separation was performed to obtain a liquid product.
[0134] (2) adding sodium hydroxide to the liquid product obtained in step (1) while stirring to adjust the pH of the system to 4.7 to obtain aluminum hydroxide precipitate, washing the aluminum hydroxide precipitate five times, and calcining it in a muffle furnace at 1200° C. for 3 h to obtain aluminum oxide, taking 50 g of the aluminum oxide and stirring and mixing it with a 0.4 mol / L sulfuric acid solution to obtain an aluminum sulfate solution;
[0135] (3) dissolving 25 g of phthalic acid in dimethyl sulfoxide to obtain a phthalic acid solution, and mixing the phthalic acid solution and the aluminum sulfate solution obtained in step (2) under ultrasonic shearing conditions, wherein the ultrasonic power is 120 W, the ultrasonic time is 40 min, the shear speed is 80 r / min, and the shear stirring time is 40 min, and then the solid-liquid separation is performed, and the obtained solid product is washed 5 times with dimethyl sulfoxide, and then freeze-dried at -50°C, and finally ground and sieved to obtain fly ash-Al-MOF;
[0136] (4) 12 g of sodium percarbonate was added to 100 g of deionized water and mixed well to obtain a sodium percarbonate solution, and 12 g of fly ash-Al-MOF was added. After stirring and mixing well, the solid-liquid separation was carried out. The obtained solid product was washed with deionized water for 5 times and freeze-dried at -50°C to obtain a fly ash-Al-MOF material loaded with sodium percarbonate.
[0137] Comparative Example 3
[0138] A method for preparing fly ash-Al-MOF material loaded with acid-containing ferrous sulfate comprises the following steps:
[0139] (1) 50 g of fly ash was placed in a muffle furnace and heat treated at 300° C. for 24 h. After the treatment, it was cooled and then added to a 0.6 mol / L sulfuric acid solution. The mixture was stirred at 70 r / min for 40 min and then solid-liquid separation was performed to obtain a liquid product.
[0140] (2) adding sodium hydroxide to the liquid product obtained in step (1) while stirring to adjust the pH of the system to 4.7 to obtain aluminum hydroxide precipitate, washing the aluminum hydroxide precipitate five times, and calcining it in a muffle furnace at 1200° C. for 3 h to obtain aluminum oxide, taking 50 g of the aluminum oxide and stirring and mixing it with a 0.4 mol / L sulfuric acid solution to obtain an aluminum sulfate solution;
[0141] (3) dissolving 25 g of phthalic acid in dimethyl sulfoxide to obtain a phthalic acid solution, and mixing the phthalic acid solution and the aluminum sulfate solution obtained in step (2) under ultrasonic shearing conditions, wherein the ultrasonic power is 120 W, the ultrasonic time is 40 min, the shear speed is 80 r / min, and the shear stirring time is 40 min, and then the solid-liquid separation is performed, and the obtained solid product is washed 5 times with dimethyl sulfoxide, and then freeze-dried at -50°C, and finally ground and sieved to obtain fly ash-Al-MOF;
[0142] (4) 24 g of ferrous sulfate, 48 g of citric acid and 100 g of deionized water were mixed to obtain an acid-containing ferrous sulfate solution, and 12 g of fly ash-Al-MOF was added. After stirring and mixing, the solid-liquid separation was carried out. The obtained solid product was washed with deionized water for 5 times and freeze-dried at -50°C to obtain a fly ash-Al-MOF material loaded with acid-containing ferrous sulfate.
[0143] Application testing:
[0144] The fly ash-Al-MOF materials loaded with sodium percarbonate and acid-containing ferrous sulfate prepared in Examples 1-12, the sodium percarbonate prepared in Comparative Example 1, the fly ash-Al-MOF materials loaded with sodium percarbonate prepared in Comparative Example 2, and the fly ash-Al-MOF materials loaded with acid-containing ferrous sulfate prepared in Comparative Example 3 were used as soil remediation agents to remediate organic contaminated soil: 20 g of petroleum hydrocarbon contaminated soil was air-dried and large stones were removed; the moisture content and petroleum hydrocarbon concentration of the contaminated soil were measured, and the petroleum hydrocarbon concentration test was carried out according to the Petroleum Hydrocarbons in Soil and Sediment (C 10 -C 40 ) was determined by gas chromatography (HJ 1021-2019), and the concentration of organic pollutants was measured to be 9800 mg / kg. The soil remediation agent was added to the contaminated soil at a dosage of 5%, and the mixture was stirred evenly. Deionized water was added during the process to adjust the soil moisture content to 25-28%. The soil was cured for 7 days to obtain the remediated soil. The concentration of petroleum hydrocarbons in the remediated soil was tested, and the remediation efficiency of the petroleum hydrocarbon-contaminated soil was calculated.
[0145] In addition, when the fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate prepared in Example 7 is used as a soil remediation agent for remediating organic contaminated soil, the curing time is increased to 14d, 28d, 60d, 90d, and 120d. The concentration of petroleum hydrocarbons in the remediated soil obtained after different curing times is tested, and the remediation efficiency of the petroleum hydrocarbon contaminated soil is calculated.
[0146] The repair efficiency is calculated according to the following formula:
[0147]
[0148] The repair efficiency test results are shown in Table 2-3:
[0149] Table 2 Remediation effect of soil remediation agents prepared in Examples 1-12 and Comparative Examples 1-3 on organic contaminated soil
[0150]
[0151] Table 3 The remediation effect of the soil remediation agent prepared in Example 7 on organic contaminated soil
[0152]
[0153] It can be seen from the test results in Table 2 that the soil remediation agents prepared in Examples 1-12 of the present invention have better remediation effects on petroleum hydrocarbon contaminated soil.
[0154] It can be seen from the test results in Table 3 that the soil remediation agent prepared in Example 7 of the present invention can achieve long-term, stable and effective remediation of petroleum hydrocarbon contaminated soil with high remediation efficiency.
Claims
1. A method for preparing fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate, characterized in that: The steps include: (1) heat-treating fly ash, cooling it after completion, and then adding it to a sulfuric acid solution, stirring and mixing it evenly, and then performing solid-liquid separation to obtain a liquid product; (2) adding sodium hydroxide to the liquid product obtained in step (1) while stirring to adjust the pH of the system to 4.5-6 to obtain aluminum hydroxide precipitate, washing and calcining the aluminum hydroxide precipitate to obtain aluminum oxide, and stirring and mixing the aluminum oxide with a sulfuric acid solution to obtain an aluminum sulfate solution; (3) dissolving phthalic acid in dimethyl sulfoxide to obtain a phthalic acid solution, mixing the phthalic acid solution and the aluminum sulfate solution obtained in step (2) uniformly, and then separating the solid and liquid, washing the obtained solid product, freeze-drying it, and finally grinding and sieving it to obtain fly ash-Al-MOF; (4) adding sodium percarbonate to deionized water, mixing uniformly to obtain a sodium percarbonate solution, adding fly ash-Al-MOF, stirring and mixing uniformly, and then separating the solid and liquid, washing the obtained solid product, and freeze-drying it to obtain fly ash-Al-MOF loaded with sodium percarbonate; (5) mixing ferrous sulfate, citric acid and deionized water to obtain an acid-containing ferrous sulfate solution, adding fly ash-Al-MOF, stirring and mixing evenly, and then separating the solid and liquid, washing the obtained solid product, and freeze-drying it to obtain fly ash-Al-MOF loaded with acid-containing ferrous sulfate; (6) Evenly mixing the fly ash-Al-MOF loaded with sodium percarbonate and the fly ash-Al-MOF loaded with acid-containing ferrous sulfate to obtain; In step (3), the mass ratio of phthalic acid to aluminum oxide is 1:(0.5-4).
2. The method for preparing fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate as claimed in claim 1, characterized in that: In step (1), the heat treatment temperature is 300-400°C and the time is 20-30h.
3. The method for preparing fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate as claimed in claim 1, characterized in that: In step (1), the concentration of the sulfuric acid solution is 0.4-0.8 mol / L.
4. The method for preparing fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate as claimed in claim 1, characterized in that: In step (2), the calcination temperature is 1100-1300° C. and the calcination time is 2-4 hours.
5. The method for preparing fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate as claimed in claim 1, characterized in that: In step (3), the mass ratio of phthalic acid to aluminum oxide is 1:
2.
6. The method for preparing fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate as claimed in claim 1, characterized in that: In steps (3), (4) and (5), the freeze-drying temperature is -50°C.
7. The method for preparing fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate as claimed in claim 1, characterized in that: In step (4), the mass ratio of sodium percarbonate to fly ash-Al-MOF is 1:
1.
8. The method for preparing fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate as claimed in claim 1, characterized in that: In step (5), the mass ratio of ferrous sulfate to citric acid is 1:2, and the mass ratio of fly ash-Al-MOF to ferrous sulfate is 1:
2.
9. The method for preparing fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate according to any one of claims 1 to 8, characterized in that: In step (6), the mass ratio of the fly ash-Al-MOF loaded with sodium percarbonate to the fly ash-Al-MOF loaded with acid-containing ferrous sulfate is 1:(1.5-3).
10. Application of fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate prepared by the method according to any one of claims 1 to 9 in repairing organic contaminated soil: air-dry the organic contaminated soil and remove large stones, then test the moisture content and organic pollutant concentration of the organic contaminated soil, add the fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate prepared by the method according to any one of claims 1 to 9 according to the tested organic pollutant concentration, stir evenly, add deionized water to adjust the moisture content to 24-28%, and maintain for 7 days to obtain repaired soil; The amount of fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate added is determined according to the concentration of organic pollutants, specifically: when the concentration of organic pollutants is ≤5000 mg / kg, the amount of fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate added is 3% of the total mass of the organic polluted soil; when the concentration of organic pollutants is 5000 mg / kg<the concentration of organic pollutants is ≤10000 mg / kg, the amount of fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate added is 5% of the total mass of the organic polluted soil; when the concentration of organic pollutants is 10000 mg / kg<the concentration of organic pollutants is ≤15000 mg / kg, the amount of fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate added is 8% of the total mass of the organic polluted soil; when the concentration of organic pollutants is greater than 15000 mg / kg, the amount of fly ash-Al-MOF material loaded with sodium percarbonate and acid-containing ferrous sulfate needs to be increased by 3% for every 5000 mg / kg increase in concentration.
Citation Information
Cited By
Improved groundwater remediation agent and preparation method thereof
CN120622647A
An improved groundwater remediation agent and its preparation method
CN120622647B
Efficient repairing agent for acid soil and preparation method of efficient repairing agent
CN120843114A
A highly efficient remediation agent for acidic soils and its preparation method
CN120843114B